Nisin Influence on the Antimicrobial Resistance Ability of Canine Oral Enterococci - Eva Cunha; Rita Janela; Margarida Costa; Luís Tavares; Ana Salomé Veiga; Manuela Oliveira (MDPI AG, 2020)
Periodontal disease (PD) is one of the most common diseases in dogs. Although previous studies have shown the potential of the antimicrobial peptide nisin for PD control, there is no information regarding its influence in the development of antimicrobial resistance or horizontal gene transfer (HGT). Nisin's mutant prevention concentration (MPC) and selection window (MSW) were determined for a collection of canine oral enterococci. Isolates recovered after the determination of the MPC values were characterized for their antimicrobial profile and its nisin minimum inhibitory and bactericidal concentrations. The potential of vanA HGT between Enterococcus faecium CCGU36804 and nine clinical canine staphylococci and enterococci was evaluated. Nisin MPC values ranged from 400 to more than 600 μg/mL. In comparison with the original enterococci collection, the isolates recovered after the determination of the nisin MPC showed increased resistance towards amoxicillin/clavulanate (5%), vancomycin (5%), enrofloxacin (10%), gentamicin (10%) and imipenem (15%). The HGT of vanA gene was not observed. This work showed that nisin selective pressure may induce changes in the bacteria's antimicrobial resistance profile but does not influence horizontal transfer of vanA gene. To our knowledge, this is the first report of nisin's MPC and MSW determination regarding canine enterococci.